Examining the determinants of social shopping behaviour among Malaysian social media users / Zulaiha Ahmad … [et al.] - Ahmad, Zulaiha; Azizan, Farah Lina; Mohd Shuib, Nor Atiqah; Md Nor, Mohamad Niza; Mat Noor, Ahmad Nizan (Universiti Teknologi MARA (UiTM), 2022)
Growing trend shopping using social media (eg. Facebook, Instagram, Twitter) become phenomenon among Malaysian digital consumers. Taking advantage of the social networking capabilities and development of Web 2.0 drastically has changed the pattern of buying behavior. Today, social shopping already replaces brick and mortar store since the consumers feel that the new channels offering an easier way to make purchases. Thus, this study relevant to be conducted. Therefore, the main objective of this study is to examine the predictors that affect social shopping behavior among Malaysian social media users. A questionnaire survey via hands on and Google Form in the Facebook were selected as data collection technique. Data were collected among 300 respondents in one of the higher education institutions located at Peninsular Malaysia. The analysis was conducted using Statistical Package for Social Sciences (SPSS) software. Multiple regression analysis was used to analyze the data. The result indicated that perceived ease use, web interactivity and trust were positively and significantly related to social shopping behavior. However, E-service quality did not predict social shopping behavior. Based on the result, it was found that trust has the strongest predictor with social shopping behavior.